Effect of Cinnamon (Cinnamomum Burmanni) Aromatherapy on Primary Dysmenorrhea Pain in Students at Air Batu High School in 2021 - Niasty Lasmy Zaen (Science Midwifery, 2021)
Primary dysmenorrhea is pain that arises from the first day of menstruation and will recover immediately after stabilizing the body's hormones. In addition to pharmacological therapy, one of which is to reduce dysminorrhea pain without drugs, namely by non-pharmacological therapy, one of which is Cinnamon (Cinnamomum burmanii), Cinnamon. (Cinnamomum burmanii) is a kind of spice-producing tree, the purpose of this study was to determine whether there was an effect of Cinnamon Aromatherapy (Cinnamomum Burmanni) on Primary Dysmenorrhea Pain in Students at SMA Negeri 1 Air Batu in 2021. This study used a pre-experimental research type, one group pre and post test design, which involved one group of subjects, the population in this study were all female students of SMA Negeri 1 Air Batu class I with 28 female students, II 30 female students and III female students. 30, which has been collected as many as 80 students, the sample sample with the purposive sampling technique. So the number of samples in this study were 44 students, with the research technique using the Wilcoxon test. The results of this study have a significant effect of giving cinnamon aromatherapy (Cinnamomum Burmanni) on primary dysmenorrhea pain in students at SMA Negeri 1 Air Batu in 2021, with the value of statistical test results using the Wilcoxon test obtained p = 0.000 (p < 0.05). The conclusions in this study from these results prove that giving cinnamon aromatherapy (Cinnamomum Burmanni) can effectively reduce the level of primary dysmenorrhea pain in students at SMA Negeri 1 Air Batu in 2021, Suggestions for health education This study proves that cinnamon aromatherapy can reduce primary dysmenorrhea. Therefore, this research can provide information and the development of nursing science, especially the sexuality block of the benefits of cinnamon aromatherapy on primary dysmenorrhea.